2009
DOI: 10.1371/journal.ppat.1000640
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus Infection Alters Neuronal Activity and Connectivity In Vitro

Abstract: Alpha-herpesviruses, including human herpes simplex virus 1 & 2, varicella zoster virus and the swine pseudorabies virus (PRV), infect the peripheral nervous system of their hosts. Symptoms of infection often include itching, numbness, or pain indicative of altered neurological function. To determine if there is an in vitro electrophysiological correlate to these characteristic in vivo symptoms, we infected cultured rat sympathetic neurons with well-characterized strains of PRV known to produce virulent or att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 73 publications
6
82
0
Order By: Relevance
“…To mention one more example in support of this model, while herpesviruses can spread through neurological synapses, they can also establish new cell-cell contacts outside the synapse to promote viral spread to neighboring cells (28,108). The ability to use viral glycoprotein/receptor pairs with dominant adhesion features will also allow viruses to manipulate existing synapses (78,126).…”
Section: Cams and Vams: Viral Mimicry Of Cell Adhesion Moleculesmentioning
confidence: 96%
“…To mention one more example in support of this model, while herpesviruses can spread through neurological synapses, they can also establish new cell-cell contacts outside the synapse to promote viral spread to neighboring cells (28,108). The ability to use viral glycoprotein/receptor pairs with dominant adhesion features will also allow viruses to manipulate existing synapses (78,126).…”
Section: Cams and Vams: Viral Mimicry Of Cell Adhesion Moleculesmentioning
confidence: 96%
“…Concentration of EFF-1 to cell borders prior to and during fusion has been observed in vivo in C. elegans as well as in heterologous systems 2,[38][39][40] . In contrast, a study of endogenous EFF-1 in the embryonic hypodermis has suggested only transient localization of EFF-1 to the membrane for fusion 37 . Some authors have postulated that this discrepancy may be related to how closely two fusing cells are apposed 40 .…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, even within the hypodermis of the animal, the localization pattern appears to differ between the embryonic and larval stages of development. Localization studies in the embryo suggested only transient localization of EFF-1 to the membrane 37 , whereas in larvae, there was clear accumulation of EFF-1 at the site prior to fusion 82 . It has been postulated that this discrepancy may be due to differences in the extent of cellular apposition at these different proteins.…”
Section: Post-translational Regulation Of Eff-1mentioning
confidence: 89%
See 2 more Smart Citations